Evaluating emplacement temperature of a 1000-year sequence of mass flows using paleomagnetism of their deposits at Mt. Taranaki, New Zealand - Lerner, Geoffrey A; Cronin, Shane J; Turner, Gillian M (Volcanica, 2019)
Temperature can be an important characteristic used to distinguish primary pyroclastic density currents or block-and-ash flows from other collapses not primarily related to an eruption, and also governs the type and level of hazard presented by these mass flows. We examined several mass-flow deposits within the AD1000-1800 Maero Formation at Mt. Taranaki, New Zealand, for field characteristics of hot emplacement - such as the presence of charcoal, baking of soils, or gas-elutriation piping - and conducted a paleomagnetic study of their thermoremanent magnetization (TRM) to determine emplacement temperatures. Results show that the majority of the deposits result from block-and-ash flows emplaced over ~500°C. Some of these deposits were indistinguishable in the field from a re-worked or low-temperature emplaced lahar or landslide deposit, indicating that sedimentary features are not a clear determinant of high emplacement temperature. The high emplacement temperatures suggest that the time between dome emplacement and collapse during this period was usually brief (<30 years), with some events consisting of rapid and repeated growth and collapse of lava domes, possibly within the same prolonged lava effusion episode.